Neural Correlates of Creativity in Analogical Reasoning. - Green, Adam E.; Fugelsang, Jonathan A.; Dunbar, Kevin N.; Kraemer, David J. M.; Gray, Jeremy R. (Journal of Experimental Psychology. Learning, Memory & Cognition, 2012)
Brain-based evidence has implicated the frontal pole of the brain as important for analogical mapping. Separately, cognitive research has identified semantic distance as a key determinant of the creativity of analogical mapping (i.e., more distant analogies are generally more creative). Here, we used functional magnetic resonance imaging to assess brain activity during an analogy generation task in which we varied the semantic distance of analogical mapping (as derived quantitatively from a latent semantic analysis). Data indicated that activity within an a priori region of interest in left frontopolar cortex covaried parametrically with increasing semantic distance, even after removing effects of task difficulty. Results implicate increased recruitment of frontopolar cortex as a mechanism for integrating semantically distant information to generate solutions in creative analogical reasoning.